Star of Persia : [large type] Esther's story - Smith, Jill Eileen, 1958- (Thorndike Press, a part of Gale, a Cengage Company, 2020)
"To complete a war his father had planned to win, King Xerxes calls every official in his vast kingdom to his palace in Susa to strategize and feast. Following that, a week of frivolity ends in the banishment of his favorite wife, something he never intended. But when he discovers Esther, Xerxes is sure he has a second chance at happiness. In her wildest dreams, Esther could never have imagined that she would end up as queen of Persia. Yet she knows better than to become complacent. Caught in the middle of palace politics, Esther will find herself in an impossible position: risk her life or consign her people to annihilation" -page [4] of cover